Hawksbill (Eretmochelys imbricata) and Green Turtle (Chelonia mydas) Nesting and Beach Selection at Príncipe Island, West Africa - Ferreira, Rogério L. (2019)
Hawksbills (Eretmochelys imbricata) and green turtles (Chelonia mydas) are the predominant nesting sea turtle species on the beaches of Príncipe Island in the Gulf of Guinea. The extent of nesting has been largely unknown, but such information is essential for management and conservation. Our study is the first island-wide nesting assessment. Results from the survey, conducted from 1 December 2009 to 18 January 2010 (during peak nesting season), show that the potential suitable nesting area (10 km) is scattered around the island’s 50 beaches. Sea turtles nested on 32 of the beaches (hawksbills, 20; green turtles, 28) and used 7.5 km of the suitable nesting habitat (hawksbills, 5.8 km; green turtles, 7.0 km). We estimated that 101 (95% CI = 86–118) clutches were deposited by 17-29 hawksbills and 1088 (95% CI = 999–1245) clutches were deposited by 166-429 green turtles on Príncipe from November 2009 to February 2010 (nesting season). Long-term green turtle nest count data collected from 2007/08 to 2015/16 suggest a positive trend. Analyses of clutch densities in relation to beach characteristics suggested that both species preferred areas where human presence is lower, which coincided with the most sheltered areas. These findings should be used to inform coastal planning and minimize impacts on nesting beaches, as Príncipe is currently targeted for tourism development. Overall, results highlight that Príncipe beaches are very important for the conservation of West African hawksbill and green turtle populations.